1996
DOI: 10.1042/bj3170017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative denitrification of Nω-hydroxy-l-arginine by the superoxide radical anion

Abstract: The superoxide radical anion (O2-.) produced during the catalytic activity of nitric oxide synthase (NOS) and cytochrome P-450 has been implicated in the oxidative denitrification of hydroxyguanidines ( > C = NOH). The reactivity of the radiolytically generated O2-. radical with N omega-hydroxy-L-arginine (NHA) is pH dependent and appears to parallel the prototropic equilibrium of the hydroxyguanidino group ( > C = NOH reversible > C = NO(-)+H+; pK = 8). The N omega-hydroxyguanidino group is more reactive towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…This indicates that the oxidizing agent in the two cases is not the same. Based on the known reactions of free riboflavin (22), the fate of superoxide in aqueous solutions (23), and the observed redox kinetic behavior of flavin in AtCRY1 described above, we postulate the following reaction schemes.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the oxidizing agent in the two cases is not the same. Based on the known reactions of free riboflavin (22), the fate of superoxide in aqueous solutions (23), and the observed redox kinetic behavior of flavin in AtCRY1 described above, we postulate the following reaction schemes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that O^ can mediate cleavage of N-hydroxyguanidines resulting in the formation of NO [4]. Moreover, radiolytically induced O^" can cleave OH-Arg [5]; the products of this reaction are NO and a cyclized carbodiimide, without the concomitant formation of citrulline.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sennequier et al have shown that Superoxide anion (OJ) can induce the formation of nitrogen oxides by oxidation of A^-hydroxyguanidines [4]. Furthermore, Everett et al have shown that radiation induced 0^~ mediates denitrification of OH-Arg leading to NO and cyclized carbodiimide [5]. A biological role of this alternative pathway of NO synthesis is suggested by the fact that the intermediate product of enzymatic nitric oxide synthesis, OH-Arg, is elevated in sera of animals treated with LPS [6] and is secreted together with NO in vivo and in vitro, as an adduct [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the discrepancy in our findings and those of Perry and Marletta (13) 14 C]citrulline, whereas we determined the production of NO by the hemoglobin assay. The oxidation of guanidoximes such as N-hydroxyarginine is catalyzed by a variety of oxidizing systems, including cytochrome P450 (26), horseradish peroxidase/H 2 O 2 (27), hemoglobin (II), H 2 O 2 alone (28), and superoxide (29,30). This oxidation primarily produces nitrites or nitrates rather than NO.…”
Section: Figmentioning
confidence: 99%